About new methods of analysis of high-speed melts streamings for the systems of computer-aided modelling of foundry processes - O. I. Chichko; V. F. Sobolev (Литьë и металлургия, 2002)
The computer methods of calculation of speed distribution of melt elements in a gating system and cast are examined. There are offered energetic measures, based on speed character and its components, for estimation of melt flow in a gating system and choice of variants of metal supply to the mode.